High Glucose-Induced TRPC6 Channel Activation Decreases Glutamate Uptake in Rat Retinal Müller Cells - Ma, Mingming; Zhao, Shuzhi; Zhang, Jian; Sun, Tao; Fan, Ying; Zheng, Zhi (Frontiers in Pharmacology, 2020)
High glucose (HG) increases the production of reactive oxygen species (ROS), leading to decreased glutamate uptake in Müller cells. The transient receptor potential cation channel 6 (TRPC6) channel, an oxidative stress-sensitive Ca2+-permeable cationic channel, is readily detected in Müller cells and highly expressed under HG conditions. Yet, the effect of high glucose-induced TRPC6 channel activation in Müller cells is poorly understood. We hypothesized that TRPC6 channel activation mediates high glucose-induced decreases in Müller cell glutamate uptake. We found RNA interference (RNAi) of the TRPC6 channel abolished HG-induced decreases in glutamate uptake and cell death. HG also decreased the expression of the glutamate-aspartate transporter (GLAST), which is the most important transporter involved in glutamate uptake. The mRNA level of ciliary neurotrophic factor (CNTF) in rMC-1 cells and the release of CNTF in the culture media was decreased, but the mRNA levels of IL-6 and vascular endothelial growth factor (VEGF) were increased under HG conditions. After RNAi silencing in rMC-1 cells, the mRNA levels of CNTF increased, but IL-6 and VEGF levels decreased. Furthermore, TRPC6 knockdown (KD) decreased expression of glial fibrillary acidic protein (GFAP) and increased expression of Kir4.1, pointing to inhibition of HG-induced gliosis in rMC-1 cells. ROS and intracellular Ca2+ levels decreased after TRPC6 knockdown. Exposure to Hyp9 (10 μM), a highly selective TRPC6 channel agonist, can aggravate HG-induced pathological changes. Collectively, our results suggest TRPC6 channel activation is involved in HG-induced decreases in glutamate uptake in rMC-1 cells. These findings provide novel insights into the role of TRPC6 in HG-induced retinal neurovasculopathy and suggest TRPC6 is a promising target for drug development for diabetic retinopathy (DR).